2016
DOI: 10.1021/acs.jpcc.6b07434
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Structures of MgO, CaO, and SrO (001) Surfaces

Abstract: Using density functional theory (PBE functional), we show that the degree of surface hydroxylation increases in the MgO, CaO, SrO series, accompanied by an increase in water adsorption energy. Already for water coverage of two monolayers, structures with dissolved M 2+ ions are considerably more stable than the intact, nondissolved surface. The dissolved ions above the surface form different patterns including ordered ones (e.g., an infinite stripe) that are preferred for MgO(001) and CaO(001) and disordered o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Ab initio molecular dynamics simulations of multilayer water adsorption on BaO(100) have revealed facile cation dissolution and formation of hydroxylated structures . Similar phenomena were recently studied for MgO(100), where a Mg(OH) 2 ‐layered structure was predicted to be thermodynamically preferred at high chemical potentials of water . Although the barriers for Mg(OH) 2 formation or detachment of solvated Mg 2+ from the surface are unknown, it can be assumed that these processes are facile at room temperature.…”
Section: Resultssupporting
confidence: 52%
“…Ab initio molecular dynamics simulations of multilayer water adsorption on BaO(100) have revealed facile cation dissolution and formation of hydroxylated structures . Similar phenomena were recently studied for MgO(100), where a Mg(OH) 2 ‐layered structure was predicted to be thermodynamically preferred at high chemical potentials of water . Although the barriers for Mg(OH) 2 formation or detachment of solvated Mg 2+ from the surface are unknown, it can be assumed that these processes are facile at room temperature.…”
Section: Resultssupporting
confidence: 52%
“…In contrast to its ubiquity on Earth and a long history of experimental demonstration in small plants, the details of the hydration mechanism on the surface of MgO remain elusive, and this fact prevents a practical introduction of TCHS technology into the social systems. Since alkaline earth metal oxide has characteristic features in its chemical properties and especially in the interface, various kinds of experimental and computational , research have been reported so far, but the research aimed at the thermochemical application is limited at the present time. …”
Section: Discussionmentioning
confidence: 99%
“…As for computational studies, many calculations have been reported on the physical/chemical properties of MgO due to its unique and interesting character. Most of these calculations discussed the surface properties of the ideal MgO lattice, , since the surface atoms of the MgO lattice were assumed to have potential catalytic activity. Although some previous calculations discussed the surface hydration step on a specific MgO surface, ,, the mechanistic details of the hydration process have not been elucidated until now. Apart from the thermal storage mechanism, Jug and co-workers reported on the water absorption structure on the MgO surface.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, limited studies have been devoted to the synthesis of two-dimensional metallic materials. In recent years, Nair et al succeeded in synthesizing MgO, CuO, and CaO metal oxide monolayers by trapping an aqueous solution of corresponding salt in graphene nanoenclosures [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%